A method of skin frictional resistant reduction by creating small bubbles at bottom of ships - Tuan, Phan Anh; Huong, Pham Thi Thanh; Quang, Vu Duy (Vietnam Journal of Mechanics, 2013)
Most of ship energy consumption spends for its propulsive device to create a propulsive force that helps the ship to win its resistant force to move forward or backward.The ship resistant is including skin frictional resistant force, wave-making resistant force and wind resistant force. This paper mentions to a method of skin frictional resistant reduction by creating small bubbles at bottom of ships. When a ship moves on/underwater surface, for skin resistant force to be generated, the ship must be in contact with the water. Skin frictional resistant force is generated by the difference in velocity between the ship and the water. Frictional resistant force will act in the direction opposite to the direction of motion of the ship. The method of skin frictional resistant reduction is injecting air flows to creating small bubbles into the turbulent boundary layer developing on the ship skin. Research found that this method may reduce ship energy consumption.This method could be applied to large ships with not high speed movement. A model ship that is scaled 1/33 of a 20000 ton cargo ship had been created for carrying out experiments in calm water and in regular wave conditions. Authors found that the highest effect from creating small bubble method on reduction ship energy consumption in calm water is 15.3% and in regular wave is 10.3%.